Association between chili pepper consumption and risk of gastrointestinal-tract cancers: A meta-analysis - Chen, Changchang; Zhang, Man; Zheng, Xutong; Lang, Hongjuan (Frontiers in Nutrition, 2022)
Background: Previous studies regarding chili pepper consumption and the risk of gastrointestinal (GI) tract cancers are inconsistent. Our aim was to estimate the direction and magnitude of the association between chili pepper consumption and the risk of GI cancers. Methods: Literature search was performed in PubMed, Embase and Web of Science databases up to 22 December, 2021. Observational studies reporting associations of chili pepper consumption with the risk of gastric cancer (GC), esophageal cancer (EC), and colorectal cancer (CRC) were included. Data extraction and quality assessment were conducted for the included literature. The summary odds ratio (OR) and 95% confidence intervals (CIs) were calculated using random-effect models. Subgroup analyses were also carried out based on cancer type, study design, region of the study, study quality, and adjustments. Results: 14 case-control studies involving 5009 GI cancers among 11310 participants were included in the meta-analysis. The summary OR showed that high consumption of chili pepper was positively related to the risk of GI cancers (OR=1.64; 95% CI: 1.00-2.70). A similar positive relation of chili pepper consumption was observed for EC risk (OR=2.71; 95% CI: 1.54-4.75), but no association with GC and CRC risk. In addition, significant associations between chili pepper intake and GI cancers were found in population-based case-control studies (OR=1.86; 95% CI: 1.07-3.22), Asian studies (OR=2.50; 95% CI: 1.23-5.08), high-quality studies (OR=1.65; 95% CI: 1.02-2.69), and studies adjusted for alcohol intake (OR=2.29; 95% CI: 1.15-4.57). Conclusion: This meta-analysis suggests that chili pepper may be a risk factor for GI cancers. Future high-quality studies should be undertaken to elucidate the underlying mechanisms. Systematic review registration: https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022320670.